Public Services A New Reform Agenda - Stoker, Gerry; Kippin, Henry; Griffiths, Simon (Bloomsbury Academic, 2013)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Griffiths, Kippin and Stoker bring together many of the country's leading academic and policy experts to explore the long-term challenges facing public services, and ask what the role of government, citizens and society should be in addressing them. The book sets out a new reform agenda, exploring possibilities for the future design and delivery of public services in the UK and beyond. Public Services: A New Reform Agenda is an important new contribution to the debate that will be invaluable for policymakers, practitioners and academics.